2013
DOI: 10.5653/cerm.2013.40.4.155
|View full text |Cite
|
Sign up to set email alerts
|

A role for endocannabinoids in acute stress-induced suppression of the hypothalamic-pituitary-gonadal axis in male rats

Abstract: ObjectiveStress is known to be an inhibitor of the reproductive hypothalamic-pituitary-gonadal (HPG) axis. However, the neural and molecular connections between stress and reproduction are not yet understood. It is well established that in both humans and rodents, kisspeptin (encoded by the kiss1 gene) is a strong stimulator of the HPG axis. In the present study we hypothesized that endocannabinoids, an important neuromodulatory system in the brain, can act on the HPG axis at the level of kiss1 expression to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 65 publications
(68 reference statements)
1
13
0
Order By: Relevance
“…administration of kisspeptin . Furthermore, in acute immobilisation stress experiments performed in rats, AM251 prevented the reduced expression of kiss1 mRNA, suggesting that kisspeptinergic neurones might be influenced by CB1 activation . For the first time, the present study shows the response of these neurones to the modulation of CB1 under LPS‐induced immune challenge.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…administration of kisspeptin . Furthermore, in acute immobilisation stress experiments performed in rats, AM251 prevented the reduced expression of kiss1 mRNA, suggesting that kisspeptinergic neurones might be influenced by CB1 activation . For the first time, the present study shows the response of these neurones to the modulation of CB1 under LPS‐induced immune challenge.…”
Section: Discussionsupporting
confidence: 50%
“…31,65 Furthermore, in acute immobilisation stress experiments performed in rats, AM251 prevented the reduced expression of kiss1 mRNA, suggesting that kisspeptinergic neurones might be influenced by CB1 activation. 66 For the first time, the present study shows the response of these neurones to the modulation of CB1 under LPS-induced immune challenge. Kisspeptinergic neurones responded by decreasing the mRNA expression of this neurotransmitter at 180 minutes post-LPS, and this effect was blocked by i.c.v.…”
Section: Discussionmentioning
confidence: 65%
“…In this way, OX hyperactivity might be responsible for the spontaneous increase in W observed in MS rats, as these lateral hypothalamic neurons have been involved in facilitating waking [12] and are activated in a variety of paradigms that involve stressors such as cold exposure, food deprivation, foot shock, and immobilization (for an extensive review, see Tsujino et al [17]). In agreement with this, it has also been demonstrated that eCBs regulate stress (for an extensive review, see Crowe et al [18]); for example, infusion of the CB1R antagonist AM251 into the ventricles of rats blocks the expression of biomarkers associated with immobilization-induced acute stress [19]. Likewise, in-vitro evidence has suggested that CB1R stimulation hyperpolarizes OX neurons and depolarizes MCH neurons in rodent brain slices [20].…”
Section: Discussionmentioning
confidence: 76%
“…Stress elevates hypothalamic endocannabinoid concentrations , likely through glucocorticoid receptor activation (Evanson et al 2010), leading to the hypothesis that ECS mediates stress-induced inhibition of the HPG axis. In support of this hypothesis, recent data demonstrate that immobilization stress-induced decrease in LH release in male rats is reversed by CB 1 R antagonist treatment (Karamikheirabad et al 2013).…”
Section: Cannabinoid Interactions With the Hypothalamic-pituitary-gonmentioning
confidence: 75%